Dynamic resilient modulus of subgrade silty clay for heavy-haul railway: an experimental investigation and the predicted method - Hao, Jianwen; Wang, Hongguo; Zhang, Xiaoning; Lin, Tao; Jiang, Xiufeng; Liu, Congcong; Li, Xiangyang (Frontiers in Earth Science, 2023)
Large-scale series of cyclic triaxial tests were conducted to explore the evolution of dynamic resilient modulus of silty clay for heavy-haul railway subgrade. A novel loading sequence for measuring dynamic resilient modulus was established, which characterized the dynamic stress state of the subgrade induced by the heavy-haul train load. In the experimental investigation, the deviator stress, confining stress, initial moisture content, and compaction degree were considered as variables and the effects of the above variables were evaluated quantitatively. The experimental results showed that the dynamic resilient modulus was negatively related to deviator stress and initial moisture content, where the average decreased rates were 14.65% and 27.79% with the increase of deviator stress from 60 kPa to 150 kPa and increase of initial moisture content from 9.8% to 15.8%, respectively. Furthermore, the dynamic resilient modulus was positively related to confining stress and compaction degree, where the average increased rates were 23.25% and 27.48% with the increase of confining stress from 20 kPa to 60 kPa and increase of compaction degree from 0.91 to 0.95, respectively. To provide a better application, the two high accuracy predicted methods were established through the empirical model and ANN approach including the above variables. This study can provide useful guideline for the effective and safe design of heavy-haul railway subgrade filled with silty clay.